FACILITATORS' PERCEIVED INSTRUCTIONAL CHALLENGES OF ONLINE FACILITATION IN OPEN AND DISTANCE LEARNING (ODL) INSTITUTIONS IN NIGERIA - ONI LEAH OLUBUNMI; BELLO LUKUMAN; OPATEYE JOHNSON; JOSIAH OWOLABI (International Studies Journal, 2025)
Online facilitation creates an online learning platform that establishes a new learning environment and provides multidimensional learning possibilities. This study focuses on the facilitators and perceived instructional challenges of online facilitation in open and distance learning (ODL) institutions in Nigeria. A cross-sectional survey research design was adopted. The population for the study consists of the open and distance learning facilitators in approved ODL universities in Nigeria. Three out of the six geopolitical zones were randomly selected, and one distance learning university was also randomly selected from each zone to make three ODL universities used for the study.  The same simple random sampling technique was adopted for the selection of facilitators in the three universities. Two hundred and two facilitators (202) participated in the study. One research question and three hypotheses were raised.  One instrument was developed, which is the Facilitators Perceived Instructional Challenges Inventory Scale (FPICIS), and a reliability coefficient value of 0.76 was obtained using Cronbach's Alpha. The data collected were analysed using descriptive and inferential statistics. The finding reveals that the mean difference in the level of significance (p > 0.05) shows that the facilitators’ age, and discipline had no significant effect on the perceived instructional challenges confronting online facilitation as a medium of instructional delivery but facilitators’ academic cadre had significant effect on perceived instructional challenges confronting online facilitation. It was therefore recommended that, in implementing online facilitation in Nigerian institutions, university management should consider the age, academic cadre, and discipline of facilitators for them to become active participants in implementing online facilitation.